Undergraduate nursing and midwifery student's attitudes to mental illness - Angela Hawthorne; Ross Fagan; Elspeth Leaver; Jessica Baxter; Pamela Logan; Austyn Snowden (Wiley, 2020)
Abstract Aim To explore levels of stigma in students of all fields of nursing and midwifery at different years and examine the impact of exposure to people with mental illness. Design A cross‐sectional survey was used. Methods The Community Attitudes to Mental Illness questionnaire was administered to all branches of student nurses (adult health, mental health, child health and learning disability) and midwives in all three years in one Higher Education Institution (HEI) in Scotland. Results Mental health nursing students scored significantly better on all stigma subscales. Stigma worsened with a little professional exposure to people with mental illness but then improved with increasing exposure. Both personal exposure and professional exposure to people with mental illness change perceptions. The professional results follow a J‐curve. Current plans for cross‐field experience involving short or virtual placements during student nurse training are likely to worsen stigma rather than improve it.